2019
DOI: 10.2147/dddt.s194765
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cathepsin G cleaves and activates IL-36&gamma; and promotes the inflammation of psoriasis</p>

Abstract: BackgroundIL-36γ is considered to be a valuable biomarker in psoriatic patients, which is expressed as an inactive precursor that needs to be proteolytically processed and activated, and neutrophil-derived proteases seemed to be potent activating enzymes of IL-36γ.ObjectivesThis study aims to investigate the activation of IL-36γ by cathepsin G (CG) and neutrophil elastase (NE).Materials and methodsWe used inactive recombinant full-length (FL)-IL-36γ with different doses of NE or CG to stimulate HaCaT cells; ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…MPO is involved in the respiratory burst and can bind to CD11b/CD18 integrins, thereby contributing to the upregulation and augmentation of neutrophil degranulation in psoriasis (86). Furthermore, the neutrophil granule-derived serine proteinases, such as NE, proteinase 3, and cathepsin G, can activate interleukin (IL)-36 cytokine and lead to the escalation of local psoriatic tissue inflammation (87, 88). Proteinase 3 cleaves and converts the resting TNFα located in membrane of epithelial cells (mTNFα) to an activated state called soluble TNFα (sTNFα), which participates in the psoriasis complex inflammatory reactions (Figure 2).…”
Section: Degranulation and Psoriasismentioning
confidence: 99%
“…MPO is involved in the respiratory burst and can bind to CD11b/CD18 integrins, thereby contributing to the upregulation and augmentation of neutrophil degranulation in psoriasis (86). Furthermore, the neutrophil granule-derived serine proteinases, such as NE, proteinase 3, and cathepsin G, can activate interleukin (IL)-36 cytokine and lead to the escalation of local psoriatic tissue inflammation (87, 88). Proteinase 3 cleaves and converts the resting TNFα located in membrane of epithelial cells (mTNFα) to an activated state called soluble TNFα (sTNFα), which participates in the psoriasis complex inflammatory reactions (Figure 2).…”
Section: Degranulation and Psoriasismentioning
confidence: 99%
“…IL-36 cytokines, such as all the IL-1 family members except for IL-1Ra, are synthesized without a signal peptide and therefore are not secreted via the endoplasmic reticulum-Golgi pathway and the mechanism of their release remains yet undefined [31]. Post-translational processing is required for full agonist or antagonist activity of all IL-36 members [5,32]. Similarly, recent in vitro and in vivo studies demonstrated that N-terminally truncated fragments of IL-38 (20–152 and 7–152 amino acid fragments) have increased biological activity compared to full-length form [33,34].…”
Section: Structural and Functional Characterization Of Il-36 Receptormentioning
confidence: 99%
“…Similarly, recent in vitro and in vivo studies demonstrated that N-terminally truncated fragments of IL-38 (20–152 and 7–152 amino acid fragments) have increased biological activity compared to full-length form [33,34]. Neutrophil-derived proteases seem to be responsible for IL-36 agonists maturation [32,35]. However, it is unclear whether truncation of IL-36 agonists and antagonists occurs in humans under pathologic conditions.…”
Section: Structural and Functional Characterization Of Il-36 Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…IL-36α seems to be activated by both NE and cathepsin-G, however, with differential patterns. Conversely, whereas cathepsin-G and proteinase-3 preferentially activate IL-36β, IL-36γ can be processed by NE, proteinase-3, cathepsin-G [12], and cathepsin-S [13], the last being particularly important for enabling the IL-36γ-related inflammation in skin psoriasis [14]. Neutrophil extracellular traps (NETs), in addition to their antimicrobial role, can also serve as a platform for the activation of IL-1α and IL-36 cytokines through NETs-associated cathepsin-G and NE [15].…”
Section: Il-36 Il-37 and Il-38: A Complex Group Of Pro- And Antimentioning
confidence: 99%